Pengaruh Konten Media Sosial Dan Electronic Word Of Mouth (EWOM) Terhadap Perilaku Konsumtif Dengan Keamanan Bertransaksi Sebagai Variabel Moderating (Studi Kasus Pengguna Tiktok di Kalangan Mahasiswa FEBI UINSU) - Alvira, Rifta (Journal of Student Development Informatics Management (JoSDIM), 2023)
The aim of this research is to analyze the influence of social media and Electronic Word of Mouth (EWOM) on consumer behavior with transaction security as a moderating variable. This study uses a quantitative approach. The sample in this study was 98 respondents who were students at the Faculty of Economics and Islamic Business, North Sumatra State Islamic University. The research instrument used a questionnaire which was analyzed using Moderated Regression Analysis (MRA). The research results show: (1) social media content has a positive and significant effect on consumptive behavior, which means that social media content can influence someone to behave consumptively; (2) Electronic Word of Mouth (EWOM) has a positive and significant effect on consumptive behavior, which means that Electronic Word of Mouth can influence someone to behave consumptively; (3) social media content and Electronic Word of Mouth (EWOM) together (simultaneously) have a positive and significant effect on consumer behavior; (4) transaction security is unable to moderate the influence of social media and Electronic Word of Mouth (EWOM) on the consumer behavior of students at the Faculty of Economics and Islamic Business, North Sumatra State Islamic University.